Validation of UBR5 as a novel PIM kinase substrate - Parikka, Johanna (My University, 2020)
The serine/threonine-specific PIM kinases have important roles in regulation of cell proliferation, survival, and motility. UBR5 is an E3 ubiquitin ligase and is involved in the regulation of gene expression, apoptosis, angiogenesis, and metabolism. UBR5 has been found to be a potential substrate for PIM kinases, although this has not yet been validated. However, both PIM kinases and UBR5 are often amplified in cancer, especially together with the well-known c-MYC oncogene. The aim of this thesis was to find evidence of interaction of PIM kinases and UBR5, and to evaluate the effects of this interaction to c-MYC expression. In MCF-7 breast cancer cells, inhibition of PIM kinase activity by the PIM-selective small molecule compound DHPCC-9 decreased UBR5 levels, whereas knock-out cells lacking expression of all three PIM family kinases had higher UBR5 levels than wild-type cells. When cells were treated with the protein synthesis inhibitor cycloheximide, the drug-induced PIM inhibition stabilized UBR5. When comparing wild-type and PIM knock-out cells, the stability of UBR5 was not affected by PIM kinases under cycloheximide-induced cell stress. The subcellular localization of UBR5 was analyzed in both wild-type and PIM knock-out cells. UBR5 was found to localize in both cytosol and nucleus in both cell fractionation, immunocytochemistry and immunofluorescence studies. No significant differences between wild-type and PIM knock-out cells were found. Additionally, c-MYC expression was decreased when UBR5 levels were higher. Although the functional relationship of PIM kinases and UBR5 could not yet be defined in this study, the results support the recent findings that UBR5 regulate cellular levels of c-MYC and that lack of PIM expression or activity decreases cellular c-MYC levels.
Keywords: PIM kinases, UBR5, c-MYC, phosphorylation